2011
DOI: 10.3233/nre-2011-0670
|View full text |Cite
|
Sign up to set email alerts
|

Virtual realities as motivational tools for robotic assisted gait training in children: A surface electromyography study

Abstract: Patient's active cooperation is essential to achieve good outcome in pediatric rehabilitation. Therefore, virtual environments were developed to enhance robotic assisted gait training. The purpose of this study was to evaluate virtual realities as motivational tools during robotic assisted gait training with children in the pediatric Lokomat . Nine children with different gait disorders and eight healthy children participated in the study. Muscular effort of the lower leg was assessed by surface electromyograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 0 publications
3
27
0
1
Order By: Relevance
“…Our results further support previous findings (Brütsch et al, 2010, 2011; Schuler et al, 2011) suggesting that a more challenging gait adaptation task can promote the motivation for active participation in the movement. It is, however, not clear to which extent this motivation is increased by the immersiveness of the VE or whether any kind of interactive feedback might have the same effect.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results further support previous findings (Brütsch et al, 2010, 2011; Schuler et al, 2011) suggesting that a more challenging gait adaptation task can promote the motivation for active participation in the movement. It is, however, not clear to which extent this motivation is increased by the immersiveness of the VE or whether any kind of interactive feedback might have the same effect.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies suggests that VE can in fact promote active participation during robotic gait training. Brütsch et al (2010, 2011) and Schuler et al (2011) showed that training with VE significantly increased active participation during robot assisted gait in children with various neurological gait disorders and healthy controls. Active participation was assessed using biofeedback values from hip and knee torques (Brütsch et al, 2010, 2011) and electromyographic activity of the lower limbs (Schuler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with our previous publication [18], and in accordance to the SENIAM guidelines, raw sEMG signals were high-pass filtered with a bi-directional zero-lag Butterworth at cut-off frequency of 10 Hz, rectified and smoothed by Root Mean Square algorithm with a time window of 100 ms to build the linear envelope [22]. For each child, for each muscle and each condition, we calculated the average sEMG pattern of 20 strides (heel strike to toe off and toe off to heel strike) of one leg, in the middle of the two minutes recording time.…”
Section: Methodssupporting
confidence: 92%
“…The test protocol was part of a more extended protocol containing five different randomly presented DGO walking conditions, each lasting 2 minutes, where training with virtual realities played an important role. A more detailed description is provided elsewhere [18]. …”
Section: Methodsmentioning
confidence: 99%